Half the sky turning oppression into opportunity for women worldwide - Kristof, Nicholas D. (New York Alfred A. Knopf, 2009)
Two Pulitzer Prize winners issue a call to arms against our era?s most pervasive human rights violation: the oppression of women in the developing world. They show that a little help can transform the lives of women and girls abroad and that the key to economic progress lies in unleashing women?s potential.
Keywords: Women?s rights -Developing countries -Case studies